(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2004)
In the present time solution of actual medical problems needs a molecular biological basis. Biomedicine a new branch on the junction of such sciences as medicine and biology – is coming up into existence. Realization of «Human Genome Project» is a brilliant example of collaboration between these two big fields of science. It is possible to apply immunogenetic data in biomedicine and particularly in transplantology. Without the knowledge of histocompatibility antigens it is impossible to characterize the donor and recipient on the one hand and on the other hand databank obtained during the DNA typing gives great opportunities and invaluable information in the study of population structure.